The Intriguing Role of Interleukin 13 in the Pathophysiology of Asthma - Marone, Giancarlo; Granata, Francescopaolo; Pucino, Valentina; Pecoraro, Antonio; Heffler, Enrico; Loffredo, Stefania; Scadding, Guy W.; Varricchi, Gilda (Frontiers in Pharmacology, 2019)
Approximately 5%–10% of asthmatic patients worldwide suffer from severe asthma. Experimental and clinical studies have demonstrated that IL-13 is an important cytokine in chronic airways inflammation. IL-13 is involved in Th2 inflammation and has been identified as a possible therapeutic target in the treatment of asthma. Two different human monoclonal antibodies (mAbs) anti-IL-13 (tralokinumab and lebrikizumab) block binding and signaling of IL-13 to its receptors, IL-13R1 and IL-13R2. Several randomized, double-blind, placebo-controlled multicenter studies have evaluated the safety and efficacy of tralokinumab and lebrikizumab in the treatment of adult patients with severe asthma, but all have failed to meet their primary end-points. No serious adverse events related to the treatment with these anti-IL-13 mAbs have been reported in these studies. These negative clinical results contrast with positive findings from blocking IL-13 signaling in experimental models of asthma, raising doubts about the transferrable value of some models. Interestingly, dupilumab, a mAb which blocks both IL-4 and IL-13 signaling reduces exacerbation rates and improves lung function in severe asthmatics. These results suggest that IL-4 and IL-13 share some, but not all functional activities in airway inflammation. Tralokinumab might show efficacy in a highly selected cohort of asthmatics characterized by overexpression of IL-13.